Analisis Potensi Pengembangan Kawasan Agropolitan yang Berkelanjutan di Kecamatan Tombolo Pao Kabupaten Gowa - Anas, Dhea Reski; Nurhidayat, M; Margie, Lucke Ayurinda (Universitas Muslim Indonesia, 2025)
Tombolo Pao District possesses significant potential for horticultural development due to its favorable agroclimate and increasing market demand. However, inadequate infrastructure hampers its development and limits the competitiveness of its superior commodities. This study analyzes the leading horticultural commodities in Tombolo Pao and evaluates existing infrastructure as a support for agropolitan development. Data collected includes secondary data on agricultural outputs and primary data on facilities and infrastructure. The analyses utilized include qualitative descriptive, location quotient (LQ), SWOT, and IFAS-EFAS methods. The LQ analysis reveals that the horticulture subsector of vegetable crops has a value of 8.07, with leading commodities including green beans 1.53, curly chili 1.48, cauliflower 1.98, cabbage 1.11, chayote 1.80, mustard greens 1.54, and tomatoes 1.93. These findings confirm horticulture as a key subsector in the district. Based on the SWOT analysis, a strategy in Quadrant I S-O strategy is recommended. This involves enhancing agribusiness efficiency through integrated zoning, research innovation, sustainable irrigation systems, and farmer training programs to improve productivity and quality. These measures aim to optimize the district's horticultural potential and support sustainable agropolitan development